The Art of Learning and Communication for Elementary School - Maryani, Anne; unita Triwardhani, Ike J; Listiani, Endri (KnE Social Sciences, 2023)
Children deserve the best education. They need to be protected, and educated properly. Education is a shared responsibility of parents, teachers, and society. The community can play a role in improving the quality of education for children. The purpose of this study was to analyze teacher communication with children in art learning and to analyze development of local creativity in art learning of elementary school at Jatisura Majalengka West Java Province Indonesia. This research was conducted in Jatisla Village, Jatiwangi District, Majalengka, West Java, Indonesia. The research method used is ethnographic communication by tracing communication patterns built from the collaborative interaction of the community, teachers, and school children. Informants are determined through sample techniques using purposive sampling. This research is expected to contribute to children’s art learning in schools. The data collection technique used is to make observations and interviews with informants, teachers, and art community activists. The research phase consisted of mapping the role of the creative community, analyzing the role of teachers in learning, and analyzing regional creativity that developed in learning. In conclusion, communication learning process in the classroom can be conveyed in various forms and communication techniques. Communication in the teaching and learning process at SD Jatisura have been doing through communication ethnography method. Interactive communication allows sharing of thoughts, ideas, feelings with one another in a way that can be understood, so that each action of communication needs and communication goals can be achieved. Communication between teachers and students is attractive and transactional, making music learning situations more effective and enjoyable. The role of the Jati Wangi Art Factory as a community, especially in the art learning of students is very large. In collaboration with teachers, we teach children how to play music using clay musical instruments, which is one of the advantages of Jatisla village. Keywords: collaboration, learning communication, community